Medication administration accuracy: using clinical observation and review of patient records to assess safety and guide performance improvement. Issue 4 (5th May 2014) - Gunningberg, Lena; Pöder, Ulrika; Donaldson, Nancy; Leo Swenne, Christine
Abstract Rationale, aims and objectives Medication‐related errors are common and can occur at every step of the medication process. The aim was to explore (1) the extent to which nurses perform fundamental safe practices related to medication administration (MA); (2) the frequency and characteristics of MA errors; and (3) the clinical significance of medication types (classes) subject to error. Methods A descriptive, exploratory cross sectional design with point in time sampling was used combining direct observations, conducted by naïve observers, and medical record review. A convenience sample of three adult surgical units was drawn from a 1000‐bed university hospital. Seventy‐two patient–nurse MA encounters were observed including 306 MA doses based on a minimum sample of 100 doses per unit. The Medication Administration Accuracy Assessment developed by the Collaborative Alliance for Nursing Outcomes in the United States was used. Results Observed adherence to MA safe practices varied between units. Identity control (9%), explaining medication to patient (11%) and medication labelled throughout the process (25%) were found to be safe practices with greatest deviation. 18% of doses involved a MA error (n = 54). Wrong time (9%) was the most common MA error, typically involving analgesics. Conclusions Given recent reports suggesting MA safe practices are strongly associated with MA errors, it is timely to strengthen RN awareness of the critical role of safe practices in MA safety. In nursing education, clinical examination using the six safe practices studied herein may enhance medication administration accuracy.